2023
DOI: 10.1001/jamainternmed.2022.5268
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Concurrent Prescription of Opioids and Gabapentin in the US, 2006 to 2018

Abstract: This cohort study examines trends in concurrent gabapentin and opioid prescribing in the US, overall and by prescriber, patient, and county characteristics, between 2006 and 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
0
17
1
Order By: Relevance
“…A clear example of these unintended consequences can be found in the campaigns to reduce opioid use and the associated rise in gabapentinoid prescriptions. A recent study of US pharmacy claims showed that between 2006 and 2018, opioid prescribing episodes plateaued, while gabapentin prescribing episodes increased 5‐fold from 1.5 to 8.1 million 2 . Though gabapentin is often perceived as a safer alternative for pain management, the evidence for its efficacy is limited, especially in older adults.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A clear example of these unintended consequences can be found in the campaigns to reduce opioid use and the associated rise in gabapentinoid prescriptions. A recent study of US pharmacy claims showed that between 2006 and 2018, opioid prescribing episodes plateaued, while gabapentin prescribing episodes increased 5‐fold from 1.5 to 8.1 million 2 . Though gabapentin is often perceived as a safer alternative for pain management, the evidence for its efficacy is limited, especially in older adults.…”
Section: Figurementioning
confidence: 99%
“…A recent study of US pharmacy claims showed that between 2006 and 2018, opioid prescribing episodes plateaued, while gabapentin prescribing episodes increased 5-fold from 1.5 to 8.1 million. 2 Though gabapentin is often perceived as a safer alternative for pain management, the evidence for its efficacy is limited, especially in older adults. A 2020 systematic review and meta-analysis of randomized trials concluded there was low quality evidence for the effectiveness of gabapentinoids, and their analgesic and opioid-sparing effects may be clinically insignificant.…”
mentioning
confidence: 99%
“…In JAMA Internal Medicine , Peet and colleagues report remarkable trends in opioid and gabapentin prescribing patterns. Between 2006 and 2018, the total volume of opiate prescriptions initially rose, but began to plateau approximately 10 years ago before falling at the end of the observational period.…”
mentioning
confidence: 99%
“…This database captures 90% of prescriptions filled at retail pharmacies in the United States. (See Peet et al, 2022. )…”
mentioning
confidence: 99%